1994
DOI: 10.1093/clinids/19.2.337
|View full text |Cite
|
Sign up to set email alerts
|

Alcoholism and Rapid Progression to AIDS After Seroconversion

Abstract: Rapid progression of infection with human immunodeficiency virus type 1 (HIV-1) to AIDS after seroconversion is rare; it has been associated with coinfection by cytomegalovirus or human T lymphotrophic virus type I. We describe an alcoholic patient whose condition progressed to AIDS 3 months after HIV-1 seroconversion occurred. Culture of peripheral blood mononuclear cells yielded a syncytium-inducing variant of HIV-1. T lymphocytes showed no spontaneous cytotoxic activity against HIV-infected cells, nor could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 9 publications
1
18
0
2
Order By: Relevance
“…[32][33][34][35][36] Our study showed significantly higher levels of HIV-1 p24 in the plasma of hu-PBL-NOD/ SCID HIVE mice chronically exposed to ethanol as compared to controls fed an isocaloric diet (Table 2). Although the effects of ethanol on HIV-1 infection still remain inconclusive, our results parallel observations in which chronic alcohol exposure in macaques infected with simian immunodeficiency virus (animal model for HIV-1 infection) resulted in high plasma viral load.…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34][35][36] Our study showed significantly higher levels of HIV-1 p24 in the plasma of hu-PBL-NOD/ SCID HIVE mice chronically exposed to ethanol as compared to controls fed an isocaloric diet (Table 2). Although the effects of ethanol on HIV-1 infection still remain inconclusive, our results parallel observations in which chronic alcohol exposure in macaques infected with simian immunodeficiency virus (animal model for HIV-1 infection) resulted in high plasma viral load.…”
Section: Discussionmentioning
confidence: 99%
“…Human studies, however, have yielded controversial information. During the pre-HAART era, Watson and colleagues (1994) suggested that alcohol may accelerate the development of AIDS, and case reports have confirmed these data (Fong et al, 1994). Nevertheless, a prospective study by Kaslow et al (1989) failed to demonstrate a relationship between percentage of CD4 cells, progression to AIDS, and alcohol use.…”
Section: Alcohol and Hiv/aids Disease Course Before And After The Eramentioning
confidence: 99%
“…With a higher density of CCR5 expressed on cell membranes, HIV would have greater opportunity to enter the cell. Beyond its effects on disease transmission, there is also evidence that alcohol allows for increased HIV replication and HIV disease progression in those already infected with HIV (Crum et al 1996;Cook et al 1997;Fong et al 1994;Bagasra et al 1993). The simplest and most obvious explanation of the behavioral link between alcohol and HIV infection is that alcohol use leads to risky sexual behaviors, although evidence of this relationship from African countries is limited.…”
Section: Introductionmentioning
confidence: 99%